EKSPLORASI KEBERADAAN GENOTIPE POTENSIAL PADI LOKAL DI WILAYAH BARAT- SELATAN ACEH - Wira Hadianto; Sumeinika Fitria Lizmah; Muhammad Jalil (Jurnal Agrotek Lestari, 2020)
The South-West Region of Aceh is one of the regions in the province of Aceh that is very rich in local rice diversity that needs to be identified and utilized as a source of genes in ssembling new superior varieties to support food security and sustainable agriculture. This study aims to determine the presence of potential local rice genotypes in the South-West Region of Aceh. This research was carried out in the South-West region of Aceh for potential local rice exploration. The survey results in the Aceh Barat-Selatan region have several potential genotypes of local rice in districts in the South-West Aceh region that are still cultivated by farmers in the south, while potential local gonotypes of rice in the South-West Aceh region, namely Aceh Jaya district: , Jantoeng, Sikleng, Ramos, Sijane, Dewi and Leukat Jeuram, West Aceh districts: Itam Tangke Lango, Head of Gidan Kinco, Lekat jero Lango, Sirendeh Semantuk Wayla and Bo Rayek Semantok Wayla. Nagan Raya Regency: Siputeh, Manyam U and Lekat Tuleng, Southwest Aceh Regency: Sigupai. South Aceh Regency: Sitandun, Silian. Simeulue Regency: Sambai and Pade Sialek. Keywords: Exploration, Local of Rice